Integrating Digital Media in Language Education: A Study on YouTube’s Effectiveness in Pronunciation Instruction - Kusuma, Suci; Mardiana, Wiwik; Iklil Saifulloh, Ahmad (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study addresses the critical gap in utilizing YouTube as an ICT tool to enhance pronunciation skills among seventh-grade students in Mojokerto. Grounded in multimedia learning theory, the research employs a descriptive qualitative approach to examine the impact of YouTube-based pronunciation lessons. Findings reveal that the teacher's strategy of creating and implementing pronunciation videos on YouTube significantly improved students' pronunciation skills and was perceived as highly effective by the learners. These results underscore the transformative potential of digital platforms like YouTube in revolutionizing English language education, particularly in pronunciation.